RISK PROFILE FOR BREAST CARCINOMA AND TUMOUR HISTOPATHOLOGY OF MEDICAL UNINSURED PATIENTS IN PAKISTAN - Raza, Uzma; Khanam, Aziza; Jabeen, Meh-; Furqan, Mohammad; Haque, Saleem -ul- (Journal of Ayub Medical College Abbottabad, 2011)
Background: Breast carcinoma is an unpredictable disease in the sense that some patients may die at early disease stage due to wide-spread metastasis within six months to one year, while others may survive longer. This study was aimed to evaluate the risk factors for breast carcinoma occurrence and histopathological features of breast carcinoma developed in the social and economical conditions of Pakistan. Methods: A total of 224 female breast cancer diagnosed patients with uncovered medical insurance visiting at the Oncology clinic of a teaching hospital at Karachi, Pakistan were selected for the study. Two hundred and twenty-four (224) healthy female subjects free of any cancer diagnosis were selected as control from different areas of the city. Information on stress, occupation, life history, and life style was obtained through personal interviews. Breast tumour pathology was evaluated for histological grade, lymph node metastasis and hormone receptor status by using standard methods. Student’s t-test, Chi-square test and ANOVA were used for comparison. Results: Breast cancer patients in significantly high percentage reported early marriages, abortion occurrence, stressful life style, family cancer history and past disease suffering from diabetes and hypertension. Life style including aerosol chewing and fat rich food intake was significantly high among the patients (p<0.05). On histopathological analysis, patients at the age of 40 years and below were identified in significantly high percentage with tumour grade III, 1-3 lymph node metastasis and hormone receptor negative type. Increasing age was associated with low tumour grade and less percentage of lymph node metastasis. Significantly high percentage of patients were presented with hormone receptor positive tumour (p<0.05). Conclusion: The contributing factors for breast carcinoma occurrence were related to life history and life-style of the patients. Medical insurance uncovered patients at initial diagnosis were presented in significantly high percentage with advanced disease including high tumour grade and lymph node metastasis due to less use of preventive and screening service which delays the diagnosis, effecting both survival and treatment cost. Keywords: Pakistan, Risk Factors, Breast cancer, Women